Molecular Docking and In Vitro Antibacterial Properties of Several Chalcone Derivatives - Susy Yunita Prabawati; Priyagung Dhemi Widiakongko; Kurniawan Eka Yuda; Agianti Sugiyati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Chalcones are flavonoid-derived secondary metabolites known for diverse biological activities, including antibacterial effects. This study investigates the antibacterial properties of two chalcone derivatived i.e. 4-dimethylamino-4-hydroxychalcone (DMAHC) and 6-fluoro-2-chloro-4-hydroxychalcone (FCHC) against Staphylococcus aureus and Escherichia coli through integrated in vitro and in silico analyses. Antibacterial activity assessed using the agar diffusion method at concentrations of 1; 5; and 10% (w/v) revealed that DMAHC exhibited dose-dependent inhibition of both bacterial species, whereas FCHC demonstrated activity only against S. aureus. Molecular docking was performed using target proteins from S. aureus (1MWT) and E. coli (7ONW). Both chalcones were capable of binding to the active-site residues of the respective proteins; however, DMAHC showed a more favorable binding affinity toward E. coli (deltaG = -7.04 kcal/mol) compared to FCHC (deltaG = -6.75 kcal/mol). Despite its negative binding energy, FCHC failed to inhibit E. coli in vitro, likely due to reduced membrane permeability associated with its halogen substituents. Overall, the combined results highlight DMAHC as a more promising antibacterial candidate than FCHC, particularly against Gram-negative bacteria, and underscore the importance of electron-donating substituents in enhancing chalcone bioactivity.